PENGARUH KONSENTRASI SIANIDA TERHADAP PRODUKSI EMAS - Tangkuman, Herling D.; Abidjulu, Jemmy; Mukuan, Hendra (Sam Ratulangi University, 2008)
The research has been done to study the effect of cyanide concentration on gold production. There are three step to produced gold. First is repulper, second is leaching and the last is burning. The result show that concentration of cyanide give effect in gold production. Cyanide with 100 ppm significantly different compared with cyanide with 200, 400 and 600 ppm in gold recovery. Based on statistical analysis, cyanide with 400 ppm is the best concentration in gold production.